Cytokine Profile in Early Infection by Leptospira interrogans in A/J Mice - Lorena Bavia; Íris A. de Castro; Mariane Tami Amano; Ana Maria Gonçalves da Silva; Silvio Arruda Vasconcellos; Lourdes Isaac (Journal of Immunology Research)
Leptospirosis is considered a neglected disease with an estimated more than one million cases every year. Since rodents are at the same time the main reservoir and generally asymptomatic to Leptospira infection, understanding why some animal species are resistant and others are susceptible to this infection would shed some light in how to control this important zoonosis. The innate immune response against Leptospira is mainly dependent on phagocytosis and activation of the Complement System. In this context, cytokines may drive the early control of infection and the adaptive response. Since the Complement System is important to eliminate leptospires in vivo, we investigated if Complement C5 in A/J mice would modulate the cytokine production during infection by Leptospira interrogans serovar Kennewicki type Pomona Fromm (LPF). Thus, our aim was to investigate the systemic levels of pro- and anti-inflammatory cytokines during Leptospira infection in the blood, liver, lung, and kidney on the third and sixth days of infection in A/J C5+/+ and A/J C5-/- mice. Blood levels of TNF-α, IL-6, IFN-γ, and MCP-1 reached a peak on the third day. Although both mouse strains developed splenomegaly, similar histopathological alterations in the liver and the lung, levels of pro- and anti-inflammatory cytokines were different. A/J C5+/+ mice had higher levels of liver IL-10, IL-1β, IL-12p40, and IL-12p70 and kidney IL-1β, IL-12p40, and IL-12p70 on the sixth day of infection when compared to A/J C5-/- mice. Our results showed that in A/J genetic background, the Complement component C5 modulates a cytokine profile in the liver and kidney of infected mice, which may play a role in the control of disease progression.